(untitled) (Research, Society and Development, 2022)
Objective: To establish a Conceptual Model of Pharmaceutical Care for the University Pharmacy of Faculdade Integrada Carajás, Redenção, Pará, based on ethical values, organizational competence, integration capacity and proactivity. Methodology: Action research, prospective, descriptive, and analytical. Results: The objective and subjective results are presented regarding the perceptions of students and teachers regarding the current structure and organization of the School Pharmacy, which supported the elaboration of a Conceptual Model of Pharmaceutical Care based on the strategy of realistic simulation. Conclusion: The conceptual model and tools for pharmaceutical care at the School Pharmacy of Faculdade Integrada Carajás, Redenção, Pará, was developed from a patient-centered care perspective, with interventions based on the patient’s context, his subjective experience with diseases and with drugs, finally using different communication strategies and skills development to encourage patients to participate in decisions about the possibilities of solving the identified problems.